Centrifugal Trends in Collective Bargaining - Raluca Dimitriu (Journal of Accounting and Management Information Systems (JAMIS), 2013)
Labour Law is dealing with a period of tremendous changes, which may even jeopardise its legitimacy. Solidarity between employees has lost its vigour since the organisational culture of the company shows a trend towards internal competition. Indeed, decreased union membership and increased number of collective labour agreements seems to definitely mark a new era of labour relations. Today, solidarity, a basic principle of the collective labour law, seems to have diminished; employees perceive themselves as competitors, and industrial relations are being atomized. Besides, at the European level, far from speaking of a centralization of the European collective bargaining, we are witnessing decentralization, down to the level of the national enterprises. In fact, what can be the sense of European solidarity, if the competition among workers, among workers of the old Member States and the new Member States, or among those with standard labour agreements and those with precarious work labour agreements - are higher than ever? There is indeed a centrifugal trend in collective negotiation, moving the weight centre towards the basic level of the unit within the pyramid of collective labour agreements. Under such new circumstances, the paper aims to analyse the possible future of the collective labour law and its possible future structure under the new labour paradigm.
Keywords: K31; 650; Labour law; Collective contracts; European collective bargaining; Social Dialogue